2014
DOI: 10.1002/chem.201403622
|View full text |Cite
|
Sign up to set email alerts
|

Selective Stabilization of Abasic Site‐Containing DNA by Insertion of Sterically Demanding Biaryl Ligands

Abstract: Biaryl derivatives that consist of one DNA-intercalating unit and a sterically demanding component exhibit a specific behavior towards abasic site-containing DNA (AP-DNA) as determined by thermal DNA denaturation experiments, spectrometric titrations and CD spectroscopic analysis. Specifically, these ligands strongly stabilize AP-DNA towards dissociation, whereas they do not or only marginally affect the melting temperature of regular duplex DNA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 60 publications
1
17
0
Order By: Relevance
“…Beyond covalent trapping of AP sites with reactive drugs, such as MX or analogues, several classes of noncovalent ligands were shown to selectively bind to AP sites in DNA and potentially hinder their recognition and processing by APE1 . Along these lines, polyazacyclophanes, such as bis‐acridine BisA , and bis‐naphthalenes 2,7‐BisNP‐O and 2,7‐BisNP‐NH (Figure ) bind to AP sites with high affinity and selectivity, outperforming other known ligands .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Beyond covalent trapping of AP sites with reactive drugs, such as MX or analogues, several classes of noncovalent ligands were shown to selectively bind to AP sites in DNA and potentially hinder their recognition and processing by APE1 . Along these lines, polyazacyclophanes, such as bis‐acridine BisA , and bis‐naphthalenes 2,7‐BisNP‐O and 2,7‐BisNP‐NH (Figure ) bind to AP sites with high affinity and selectivity, outperforming other known ligands .…”
Section: Introductionmentioning
confidence: 99%
“…[16] Beyond covalent trapping of AP sites with reactive drugs, such as MX or analogues,s everal classes of noncovalentl igands were shown to selectively bind to AP sites in DNA and potentially hinder their recognition and processing by APE1. [17][18][19][20][21][22] Along these lines,p olyazacyclophanes, such as bisacridine BisA, [23,24] andb is-naphthalenes 2,7-BisNP-O and 2,7-BisNP-NH ( Figure 1) bind to AP sites with high affinity and selectivity,o utperforming other known ligands. [25,26] We demonstrated that these compounds inhibited the activity of APE1 in vitro with high efficiency,c omparable to that of the best catalytic APE1 inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper we present a novel method for screening potential high‐affinity nucleobase surrogates based on double‐helical oligonucleotide probes featuring a single‐nucleotide gap flanked by a fluorescent nucleoside analogue (Scheme ). A similar method has recently been described to identify intercalators that show specific affinities for abasic sites in DNA . In our study, fluorometric titrations of the oligonucleotide probes with Pd II chelates of dipicolinamide and its N 2 , N 6 ‐dialkylated derivatives revealed base pairing preferences significantly different from those observed at monomer level, in terms of both absolute and relative stability of the various Pd II ‐mediated base pairs.…”
Section: Methodsmentioning
confidence: 72%
“…Thereupon, we established this class of ligands as versatile DNA binders, and we demonstrated over the years that annelated quinolizinium derivatives bind efficiently and selectively to duplex, triplex and quadruplex DNA as well as to DNA with abasic sites. [100][101][102][103][104][105][106] Chart 2. Comparison of 9-aminobenzo[b]quinolizinium (2f) with established DNA intercalators.…”
Section: Dna-sensitive Fluorescent Probesmentioning
confidence: 99%